Excessive and less complex body movement in children with autism during face‐to‐face conversation: An objective approach to behavioral quantification. Issue 2 (27th November 2021) - Zhao, Zhong; Tang, Haiming; Alviar, Camila; Kello, Christopher T.; Zhang, Xiaobin; Hu, Xinyao; Qu, Xingda; Lu, Jianping
Abstract: The majority of existing studies investigating characteristics of overt social behavior in individuals with autism spectrum disorder (ASD) relied on informants' evaluation through questionnaires and behavioral coding techniques. As a novelty, this study aimed to quantify the complex movements produced during social interactions in order to test differences in ASD movement dynamics and their convergence, or lack thereof, during social interactions. Twenty children with ASD and twenty‐three children with typical development (TD) were videotaped while engaged in a face‐to‐face conversation with an interviewer. An image differencing technique was utilized to extract the movement time series. Spectral analyses were conducted to quantify the average power of movement, and the fractal scaling of movement. The degree of complexity matching was calculated to capture the level of behavioral coordination between the interviewer and children. Results demonstrated that t he average power was significantly higher (p < 0.01), and the fractal scaling was steeper (p < 0.05) in children with ASD, suggesting excessive and less complex movement as compared to the TD peers. Complexity matching occurred between children and interviewers, but there was no reliable difference in the strength of matching between the ASD and TD children. Descriptive trends in the interviewer's behavior suggest that her movements adapted to match both ASD and TD movements equally well. The findings of our study might shed light on seeking novel behavioral markers of ASD, and on developing automatic ASD screening techniques during daily social interactions. Lay Summary: By implementing an objective behavioral quantifying technique, our study demonstrated that children with autism had more body movement during face‐to‐face conversation, and they moved in a less complex way. The current diagnosis of autism heavily relies on doctor's experiences. These findings suggest a potential that autism might be automatically screened during daily social interactions.